Depolarization of neurones in the isolated olfactory cortex of the guinea-pig by γ-aminobutyric acid - Brown, D.A. (1979)
1 Effects of γ-aminobutyric acid (GABA) on single neurones in slices of guinea-pig olfactory cortex maintained in vitro were recorded with single intracellular microelectrodes. The average resting potential of 52 cells was -75 mV and apparent input resistance ranged from 20 to 200 MΩ. 2 Superfusions of GABA over the slice invariably depolarized the neurones and reduced their input resistance. The minimum effective concentration was 50 to 200 μM. 3 The reversal potential for the depolarization produced by 0.1 mM GABA (E(g)) was -66 ± 2 mV. At concentrations >0.1 mM the reversal potential became progressively more positive (-55 to -50 mV). 4 Reduction of external chloride, with isethionate as the substitute anion, increased the amplitude of the depolarization. 5 GABA reduced the amplitude of the excitatory postsynaptic potential produced by lateral olfactory tract stimulation, and occluded or reversed the subsequent depolarizing recurrent inhibitory postsynaptic potential. 6 Action potentials elicited by injection of depolarizing current or by focal antidromic stimulation were slowed and reduced in amplitude by GABA. 7 The effects of GABA on membrane conductance (potency = 1) were duplicated by 3-aminopropanesulphonic acid (potency = 20), β-alanine (0.5), β-amino-n-butyric acid (0.5), glycine (0.3) and L-2,4-diaminobutyric acid (0.2). For a given conductance change, 3-aminopropanesulphonic acid, glycine and β-alanine produced less depolarization than did GABA. 8 It is concluded that the action of GABA on the neurones is compatible with a role in mediating recurrent postsynaptic inhibition.